CRITERIA FOR ASSESSING HEALTH CARE QUALITY: THE DIFFERENCES IN VIEWPOINTS - A. V. Yanichkina; V. A. Larionov; M. A. Shambatov; E. M. Vishneva (Juvenis Scientia, 2017)
The article presents the results of a survey of patients in a therapeutic hospital, doctors, students of a medical university, conducted to identify the main quality criteria, and the main defects in the provision of medical care.